Trade in services in the context of SADC-EU EPA: risks and opportunities - Lehloenya, P. M. (Faculty of Law, University of the Free State, 2012)
The desire by the EU to include trade in services as part of the ongoing EPA negotiations with SADC has brought into sharp focus the question as to whether such a move would be in the best interest of SADC. The significance of this question lies in the widely held belief among developing countries that opening up their service sectors to foreign competition while the sector remains poorly developed would harm their developmental prospects. This article examines the merits and weaknesses of this viewpoint, by highlighting the risks that often accompany liberalisation of services between two regions that are at different levels of development. It also draws attention to the growing importance of services in world trade and how they have become an indispensable component of economic growth in developing countries. The article concludes that an EPA is not the most appropriate mechanism for achieving equitable trade in services from a SADC perspective, given the adversarial nature of the negotiations that precede its conclusion. Furthermore, rather than support an all-encompassing process involving liberalisation of all the services sectors at one go, the article advocates a more gradual process involving liberalisation of a few strategic sectors at a time, which would focus within the region initially and only expand globally with time.

Onderhandelinge met die SAOG het die vraag of so ’n stap in die beste belang van die SAOG sal wees skerp onder die soeklig geplaas. Die belang van hierdie vraag lê in die algemeen aanvaarde siening onder die ontwikkelende lande dat die opening van hul diens sektore tot buitelandse mededinging, terwyl die sektor swak ontwikkeld bly, hul ontwikkelings-vooruitsigte sou benadeel. Hierdie referaat ondersoek die meriete en swakhede van hierdie siening. Klem word geplaas op die risiko’s wat dikwels die liberalisering van dienste tussen die twee streke wat op verskillende vlakke van ontwikkeling is, vergesel. Dit trek ook die aandag na die toenemende belangrikheid van dienste in wêreld handel en hoe hulle ’n onmisbare komponent van ekonomiese groei in die ontwikkelende lande geword het. Hierdie referaat kom tot die gevolgtrekking dat ’n EPA nie die mees geskikte meganisme is vir die bereiking van billike handel in dienste van ’n SAOG-perspektief nie, inaggenome die opponerende aard van die onderhandelinge wat die sluiting daarvan voorafgaan. Verder, eerder as om die ondersteuning van ’n alles-omvattende proses wat die liberalisering van al die sektore van dienste op ’n slag insluit, staan hierdie referaat ’n meer geleidelike proses wat die liberalisering van ’n paar strategiese sektore op ’n tyd toe, wat aanvanklik sal fokus binne die streek, en slegs globaal sal uitbrei met verloop van tyd.
Keywords: Southern African Development Community; Trade; Services; European Union; Economic Partnership Agreements